Reconfigurable Feeding Network with Dual-band Filter for WiMAX Application - N. Edward; Z. Zakaria; N.A. Shairi (Institute of Advanced Engineering and Science, 2017)
Design and simulation for reconfigurable Wilkinson Power Divider (WPD) related to WiMAX application is proposed in this paper. This proposed design relates to dual band WiMAX frequencies at 2.5 GHz and 3.5 GHz. The main purpose of this design is to design a switchable feeding network that can cover the WiMAX standards by reconfiguring the microstrip line length using PIN diode switches. Besides, the power divider also can be design and develop as power combiner due to the passive component structure and hence reciprocal. In this proposed Wilkinson power divider, different band of frequencies for WiMAX application are obtained by using PIN diode. By turning ‘ON’ and ‘OFF’ the PIN diode, different frequencies are achieved between 2.5 and 3.5 GHz. This proposed design used Rogers RO4350 (er = 3.48, h = 0.508mm) as a substrate material and copper (thickness = 0.002 mm) related to patch of design. This simulation results showed that the S11 is less than -15dB; and S12 and S13 are better than -5dB. Based on these simulation results, the proposed WPD design using dual-band filter was well applied where it has better return loss (S11) with less than -15 dB for both WiMAX frequencies.